The significance of monuments : on the shaping of human experience in Neolithic and Bronze Age Europe - Bradley, Richard, 1946- (Routledge, 1998)
"The book studies the importance of monuments, tracing their history for nearly three millennia from their first creation over six thousand years ago. Part I discusses how monuments developed and their role in forming a new sense of time and space among the inhabitants of prehistoric Europe. Such features of the landscape as mounds and enclosures are also examined in detail. Through a series of case studies, Part II considers how monuments were modified and reinterpreted to suit the changing needs of society." "The Significance of Monuments is an indispensable text for all students of European prehistory. It is also an enlightening read for professional archaeologists and all those interested in this fascinating period."--Jacket